Peripheral arterial disease as an independent predictor for excess stroke morbidity and mortality in primary-care patients: 5-year results of the getABI study - Meves, Saskia Hannah; Diehm, Curt; Berger, Klaus; Pittrow, David; Trampisch, Hans Joachim; Burghaus, Ina; Tepohl, Gerhart; Allenberg, Jens-Rainer; Endres, Heinz G.; Schwertfeger, Markus; Darius, Harald; Haberl, Roman L. (Cerebrovascular diseases, 2010)
Background:There is controversial evidence with regard to the significance of peripheral arterial disease (PAD) as an indicator for future stroke risk. We aimed to quantify the risk increase for mortality and morbidity associated with PAD. Methods:In an open, prospective, noninterventional cohort study in the primary care setting, a total of 6,880 unselected patients ≧65 years were categorized according to the presence or absence of PAD and followed up for vascular events or deaths over 5 years. PAD was defined as ankle-brachial index (ABI) <0.9 or history of previous peripheral revascularization and/or limb amputation and/or intermittent claudication. Associations between known cardiovascular risk factors including PAD and cerebrovascular mortality/events were analyzed in a multivariate Cox regression model. Results:During the 5-year follow-up [29,915 patient-years (PY)], 183 patients had a stroke (incidence per 1,000 PY: 6.1 cases). In patients with PAD (n = 1,429) compared to those without PAD (n = 5,392), the incidence of all stroke types standardized per 1,000 PY, with the exception of hemorrhagic stroke, was about doubled (for fatal stroke tripled). The corresponding adjusted hazard ratios were 1.6 (95% confidence interval, CI, 1.1-2.2) for total stroke, 1.7 (95% CI 1.2-2.5) for ischemic stroke, 0.7 (95% CI 0.2-2.2) for hemorrhagic stroke, 2.5 (95% CI 1.2-5.2) for fatal stroke and 1.4 (95% CI 0.9-2.1) for nonfatal stroke. Lower ABI categories were associated with higher stroke rates. Besides high age, previous stroke and diabetes mellitus, PAD was a significant independent predictor for ischemic stroke. Conclusions:The risk of stroke is substantially increased in PAD patients, and PAD is a strong independent predictor for stroke.